Bacteroides acidifaciens in the gut plays a protective role against CD95-mediated liver injury. (31st December 2022) - Wang, Hesuiyuan; Wang, Qing; Yang, Chengmao; Guo, Mingming; Cui, Xiaoyue; Jing, Zhe; Liu, Yujie; Qiao, Wanjin; Qi, Hang; Zhang, Hongyang; Zhang, Xu; Zhao, Na; et al.
ABSTRACT: The intestinal flora plays an important role in the development of many human and animal diseases. Microbiome association studies revealed the potential regulatory function of intestinal bacteria in many liver diseases, such as autoimmune hepatitis, viral hepatitis and alcoholic hepatitis. However, the key intestinal bacterial strains that affect pathological liver injury and the underlying functional mechanisms remain unclear. We found that the gut microbiota from gentamycin (Gen)-treated mice significantly alleviated concanavalin A (ConA)-induced liver injury compared to vancomycin (Van)-treated mice by inhibiting CD95 expression on the surface of hepatocytes and reducing CD95/CD95L-mediated hepatocyte apoptosis. Through the combination of microbiota sequencing and correlation analysis, we isolated 5 strains with the highest relative abundance, Bacteroides acidifaciens (BA), Parabacteroides distasonis (PD), Bacteroides thetaiotaomicron (BT), Bacteroides dorei (BD) and Bacteroides uniformis (BU), from the feces of Gen-treated mice. Only BA played a protective role against ConA-induced liver injury. Further studies demonstrated that BA-reconstituted mice had reduced CD95/CD95L signaling, which was required for the decrease in the L-glutathione/glutathione (GSSG/GSH) ratio observed in the liver. BA-reconstituted mice were also more resistant to alcoholic liver injury. Our work showed that a specific murine intestinal bacterial strain, BA, ameliorated liver injury by reducing hepatocyte apoptosis in a CD95-dependent manner. Determination of the function of BA may provide an opportunity for its future use as a treatment for liver disease.